Zur Ökonomik der Kontrollmaßnahmen bei Lebensmitteln und Futtermitteln; Economics of Food and Feedstuffs Safety with Special Regard to Law Enforcement - Christian Lippert (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– The objective of this article is to describe and to analyse the basic relationships between control frequency, amount of fines, other social sanctions, the producers' capability to influence certain attributes (including costs of quality assurance) and damage incidence in the field of food and feedstuffs safety. For this purpose an economic model is developed that minimizes monitoring costs including (a) the harm prevented and (b) the revenues from fines. First, monitoring measures are optimized by exclusively taking account of the interests of consumers and taxpayers. In a second step, the model is enlarged by adding constraints relative to the costs of quality assurance so that aspects of both producer welfare and total social costs are explicitly accounted for when simultaneously optimizing the probability of detection and the degree of punishment.The results derived from the model show among other things:-From an economic point of view legal regulation (i.e. the setting of performance standards) is advisable only in cases of comparatively high potential damages.-Even when the entire production is to be free from certain residues, it is often not necessary to check all units of the commodity considered.-In the presence of (a) poor possibilities to influence an attribute - or a wide range of quality assurance costs among producers - and (b) prospective damages which justify a control frequency of one hundred percent, no fines at all should be stipulated in order to avoid allocative distortions.-In the case of strong social sanctions (e.g. losses of reputation), all else being equal the control frequency may be lowered considerably.Against the background of these conclusions the application of uniform control frequencies is inappropriate. Instead, every food control authority should be free to choose the size of samples, taking into account not only the given structure of fines but also its knowledge concerning the market specific social sanctions, monitoring costs, the extent of potential damages from legal transgressions as well as the producers' possibilities and costs of influencing the relevant food or feedstuffs attributes.
Keywords: 330; Lebensmittelsicherheit; Informationsökonomik